Benita and the night creatures - Llanos, Mariana (Barefoot Books, 2023)
"Benita loves to read in bed but keeps getting interrupted by a whistling Tunche, a scary Supay and other spooky creatures from Peruvian lore. To the creatures' disbelief, Benita is so absorbed by her book that she's not the least bit scared of them. This humorous celebration of bedtime reading puts a global twist on taking the "scary" out of monsters"--